2009
DOI: 10.1111/j.1539-6975.2009.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐National Study of Government Social Insurance as an Alternative to Tort Liability Compensation

Abstract: Litigation rates in the United States have long been considered out of proportion with the remainder of the world, leading to a good deal of economic research trying to understand the causes. Much of that literature has focused on lawyer compensation rules and availability of general damage awards. Another possible reason for differences in national litigation rates is the relative generosity of government social programs. Using a sample of 24 countries over a 12-year period, we test the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Browne, Chung, and Frees (2000) find a positive relation between common law systems and both motor vehicle and general insurance demand. More recently, Kerr, Ma, and Schmitt (2009) document a negative relation between government social programs and the demand for auto and general liability insurance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Browne, Chung, and Frees (2000) find a positive relation between common law systems and both motor vehicle and general insurance demand. More recently, Kerr, Ma, and Schmitt (2009) document a negative relation between government social programs and the demand for auto and general liability insurance.…”
Section: Literature Reviewmentioning
confidence: 99%
“… The tort system and the availability of alternative risk transfer instruments also have a significant impact on insurer losses and, hence, insurance rates (see, e.g., Born, Viscusi, and Baker, 2009; Kerr, Ma, and Schmit, 2009). …”
mentioning
confidence: 99%
“…These results strengthen the evidence of a substitution effect existing among different sources of compensation for bodily injuries. This effect has been previously demonstrated in studies of bodily injury claims decisions for auto liability compensation (Kerr et al, 2009) and workers' compensation (Biddle & Roberts, 2003).…”
Section: Kerrmentioning
confidence: 52%
“…As Cummins and Tennyson (1996) and Kerr et al (2009) found with respect to the filing of BIL auto insurance claims and Biddle and Roberts (2003) found in terms of the propensity to file a workers' compensation claim, the existence of other sources of recovery for the bodily injury loss is an important factor. For example, the presence of personal health insurance or workers' compensation benefits will offset at least partially and sometimes completely the financial impact of injuries suffered in an auto accident effectively decreasing the benefit of filing an auto insurance claim relative to the costs, ceteris paribus.…”
Section: Characteristics Of the Lossmentioning
confidence: 91%